1997
DOI: 10.1097/00005373-199705001-00005
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Principles for Volume Regulation of a Tissue Enclosed in a Rigid Shell with Application to the Injured Brain

Abstract: We contend that in the long run, the interstitial volume in such a tissue can be reduced only through reduction in arterial inflow pressure providing an otherwise optimal therapy to improve microcirculation. Therefore we argue, in contrast to the conventional view, that antihypertensive and antistress therapy may be of value by reducing the interstitial tissue volume during treatment of brain edema, and that the problem with ischemia during such therapy can be handled when considering an otherwise optimal inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 26 publications
1
73
0
Order By: Relevance
“…1). The physiological forces that regulate fluid fluxes across the injured blood-brain barrier are actively optimized in order to reduce the postinjury edema (Asgeirsson et al, 1994;Grande et al, 1997Grande et al, , 2002. This treatment concept was introduced in our clinical practice in 1994.…”
Section: Introduction Smentioning
confidence: 99%
“…1). The physiological forces that regulate fluid fluxes across the injured blood-brain barrier are actively optimized in order to reduce the postinjury edema (Asgeirsson et al, 1994;Grande et al, 1997Grande et al, , 2002. This treatment concept was introduced in our clinical practice in 1994.…”
Section: Introduction Smentioning
confidence: 99%
“…If BBB is intact, an increase in transcapillary pressure following LP will not induce any transcapillary filtration and there will be no increase in brain tissue volume (19,20,31). This means that the CSF slit around the brain stem area remains open, and CSF communicates freely in the whole intradural space (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ICP may even be reduced to negative values. The decrease in ICP will increase transcapillary forces across the cerebral capillaries, but this increase will not induce any filtration resulting in oedema, as cerebral capillaries are impermeable for small solutes in the normal brain (intact BBB) (30)(31)(32). However, a decrease in ICP will have other haemodynamic effects in terms of disappearance of the subdural venous collapse if ICP falls below the extradural pressure (p<pv in Fig.…”
Section: Effects Of Lumbar Dural Puncture Under Normal Conditionsmentioning
confidence: 99%
“…13 The question may be raised as to whether an intracranial blood volume-reducing therapy induced by hypothermia would be as effective as the established ICP-reducing therapies, which mainly act by reducing brain oedema. [24][25][26][27] Ongoing studies…”
Section: Can Alternative Protocols Improve Outcome?mentioning
confidence: 99%
“…18 The use of vasoconstrictors is an important component to counteract hypothermia-induced reduction in arterial pressure in the ongoing study by Clifton et al 29 Even though the use of vasoconstrictors is common in the treatment of TBI patients and favoured in traditional guidelines to increase cerebral perfusion pressure, 24,25 serious concerns have been raised since almost two decades in the use of these drugs in TBI patients, as they may compromise the circulation further of the hypoxic penumbra zone. 26,27 A recent study even showed that cerebral oxygenation was negatively affected by an infusion of norepinephrine in healthy subjects. 34 …”
Section: Hypothermia-induced Use Of Vasoconstrictorsmentioning
confidence: 99%